Use of Natural Compounds as a Potential Therapeutic Agent Against COVID-19 - Wahab, Shadma; Ahmad, Irfan; Irfan, Safia; Baig, Mohammad H.; Farouk, Abd-ElAziem; Dong, Jae-June (Current Pharmaceutical Design, 2021)
The current 2019-nCoV outbreak is becoming extremely harmful and has affected the whole world. Its control is challenging because there is no effective vaccine or drug available for coronavirus disease. The Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), previously named as 2019 novel coronavirus (2019-nCoV), primarily targets the human respiratory system to lung lesions and lethal pneumonia. Natural products have always shown a crucial role in the process of drug development against various diseases. They may serve as leads for further drug development to combat emergent mutants of the coronavirus. In this review, the current status of natural compounds and their derivatives acting against different species of CoV are discussed.
Keywords: dietary supplements